Breast Screening Utilization and Cost Sharing Among Employed Insured Women Following the Affordable Care Act: Impact of Race and Income - Fazeli Dehkordy, Soudabeh (J Womens Health (Larchmt), 2019)
Introduction: We assessed changes in screening mammography cost sharing and utilization before and after the Affordable Care Act (ACA) and the revised U.S. Preventive Services Task Force (USPSTF) recommendations by race and income. Methods: We used Optum™(©) Clinformatics™(®) Data Mart deidentified patient-level analytic files between 2004 and 2014. We first visually inspected trends for screening mammography utilization and cost-sharing elimination over time by race and income. We then specifically calculated the slopes and compared trends before and after 2009 and 2010 to assess the impact of ACA implementation and USPSTF recommendation revisions on screening mammography cost-sharing elimination and utilization. All analyses were conducted in 2018. Results: A total of 1,763,959 commercially insured women, ages 40–74, were included. Comparing trends for cost-sharing elimination before and after the 2010 ACA implementation, a statistically significant but small upward trend was found among all races and income levels with no racial or income disparities evident. However, screening utilization plateaued or showed a significant decline after the 2009 USPSTF recommendation revision in all income and racial groups except for African Americans in whom screening rates continued to increase after 2009. Conclusions: Impact of ACA cost-sharing elimination did not differ among various racial and income groups. Among our population of employer-based insured women, the racial gap in screening mammography use appeared to have closed and potentially reversed among African American women. Continued monitoring of screening utilization as health care policies and recommendations evolve is required, as these changes may affect race- and income-based disparities.